Long‐term outcome of transplant ureterostomy in children: A National Review. (20th November 2020) - Costigan, Caoimhe S.; Raftery, Tara; Riordan, Michael; Stack, Maria; Dolan, Niamh M.; Sweeney, Clodagh; Waldron, Mary; Kinlough, Mairead; Flynn, Joan; Bates, Marie; Little, Dilly M.; Awan, Atif
Abstract: Background: CAKUT are the most common cause of end‐stage renal failure in children (Pediatr Nephrol. 24, 2009, 1719). Many children with CAKUT have poor urinary drainage which can compromise post‐transplant outcome. Identifying safe ways to manage anatomical abnormalities and provide effective urinary drainage is key to transplant success. Much debate exists regarding optimum urinary diversion techniques. The definitive formation of a continent urinary diversion is always preferable but may not always be possible. We explore the role of ureterostomy formation at transplantation in a complex pediatric group. Methods: We report six pediatric patients who had ureterostomy formation at the time of transplantation at the National Paediatric Transplant Centre in Dublin, Ireland. We compared renal function and burden of urinary tract infection to a group with alternative urinary diversion procedures and a group with normal bladders over a 5‐year period. Results: There was no demonstrable difference in estimated glomerular filtration rate between the groups at 5‐year follow‐up. The overall burden of UTI was low and similar in frequency between the three groups. Conclusions: Ureterostomy formation is a safe and effective option for temporary urinary diversion in children with complex abdominal anatomy facilitating transplantation; it is, however, important to consider the implications and risk of ureterostomy for definitive surgery after transplantation.